Resilience in the Vaccine Supply Chain: Learning from the COVID-19 Pandemic - Megan Hay; Anika Teichert; Sarah Kilz; Agnes Vosen (Vaccines)
Background: The COVID-19 pandemic revealed vaccine supply chain (VSC) weaknesses and enabled post-pandemic analysis highlighting the growing importance of supply chain resilience. This study analyzes weaknesses and potentials for VSC resilience from an industry perspective. Insights from this study are aimed at supporting helping managers and policy-makers build a more resilient vaccine supply. Methods: A qualitative semi-structured interview study was conducted with 12 industry experts along the VSC. The interviews were assessed concerning the learnings from the pandemic in a two-step content analysis. Codes were assigned to key VSC concepts and variables and then linked to political, economic, social, technological, legal, and environmental (PESTLE) dimensions. The complex multi-stakeholder supply chain was visualized in a system overview, highlighting main actors, roles, constraints, and resilience. Results: The analysis resulted in 60 codes, categorized into the six PESTLE dimensions and three additional (sub)groups (mRNA, Supply chain resilience, and Solutions). The largest dimension was Economic, with 39 codes, including the Supply chain resilience subgroup. Twelve stakeholder groups were identified, with purchasers, manufacturers, suppliers, developers, and regulatory agencies being the most significant in emergency vaccine manufacturing situations. Conclusions: The system overview demonstrated the VSC as a complex network of actors with unaligned goals rather than a linear supply chain. This study shows that the VSC is characterized by uncertainty due to external factors, like the unpredictability of new emergencies, and internal factors like vaccine demand. The lack of transparency between industry stakeholders exacerbates VSC disruption. We conclude that infrastructures and management practices that enable increased transparency and collaboration between stakeholders hold the greatest potential for strengthening the VSC’s resilience to future pandemics.